Tan buena Elenita Poniatowska : noticias de autores y libros - Osorio G., Jairo (Medellín : Ediciones UNAULA, 2017)
A compilation of book reviews and personal views about literature and authorship.
Online resource; title from PDF title page (Digitalia, viewed April 6, 2018)
Keywords: Books -- Reviews; Authorship; Osorio G., Jairo -- Books and reading; Book reviews; Electronic books